An autopsy case of cortical superficial siderosis with persistent abnormal behavior. Issue 6 (18th April 2016) - Torii, Youta; Iritani, Shuji; Fujishiro, Hiroshige; Sekiguchi, Hirotaka; Habuchi, Chikako; Umeda, Kentaro; Matsunaga, Shinji; Mimuro, Maya; Ozaki, Norio; Yoshida, Mari; Fujita, Kiyoshi
Abstract : In recent years, MRI has revealed cortical superficial siderosis (cSS), which exhibits hemosiderin deposition in only the cortical surface. However, the associations between the histological findings and clinical symptoms of cSS remain unclear. We herein report an autopsy case of a 75‐year‐old Japanese man with cSS with persistent abnormal behavior according to cognitive impairment, hallucination and delusion. At 73 years of age, the patient presented with unusual behavior that indicated auditory hallucination and delusion. One year later, he was admitted to the hospital for malignant lymphoma. On admission, cognitive impairment was detected by a screening test. Soon after hospitalization, he presented with active delirium including visual hallucination and delusion. The patient's excited behavior was improved by the administration of a major tranquilizer. However, the abnormal behavior and cognitive impairment persisted. At 75 years of age, he died of heart failure. A neuropathological investigation revealed hemosiderin depositions in the superficial layer of the cortex in the medial and lateral frontal lobe, the lateral temporal lobe, the parietal lobe, and the medial and lateral occipital lobe. Neuritic plaques and diffuse plaques were extensively observed, which corresponded to Braak stage C and CERAD B, although NFTs were observed that corresponded to Braak stage II. Cortical amyloid angiopathy was not observed in any regions. Ischemic change of brain was also mild. Our report suggests that localized deposition of hemosiderin in the cortex might affect the manifestation of cognitive impairments and hallucination. Further clinicopathological studies are needed to clarify the clinical manifestations of patients with cSS.